An education in Facebook? : higher education and the world's largest social network - Kent, Mike, 1969-; Leaver, Tama (New York, NY : Routledge, 2014)
'An Education in Facebook? examines and critiques the role of Facebook in the evolving landscape of higher education. At times a mandated part of classroom use, at others an informal network for students, Facebook has become an inevitable component of college life, acting alternately as an advertising, recruitment, and learning tool. But what happens when educators use a corporate product, which exists outside of the control of universities, to educate students?An Education in Facebook? provides a broad discussion of the issues educators are already facing on college campuses worldwide, particularly in areas such as privacy, copyright, and social media etiquette. By examining current uses of Facebook in university settings, this book offers both a thorough analytical critique as well as practical advice for educators and administrators looking to find ways to thoughtfully integrate Facebook and other digital communication tools into their classrooms and campuses'--
The revolution that's already happening / Mike Kent and Tama Leaver -- Challenges and opportunities in using Facebook to build a community for students at a UK university / Nick Pearce --'We use Facebook chat in lectures of course!' Exploring the use of a Facebook group by first-year undergraduate students for social and academic support / Eve Stirling -- Facebook as a student development tool / Shane Tilton -- Beyond friending: psychosocial engagement on Facebook and its implications for academic success / Catherine McLoughlin and Mark J. W. Lee -- What's on your mind? Facebook as a forum for learning and teaching in higher education / Mike Kent -- Academic armour: social etiquette, social media and higher education / Collette Snowden and Leanne Glenny -- Exploring Facebook groups' potential as teaching-learning environment for supervision purposes / Mona Hajin -- How social should learning be? Facebook as a learning management system / Tauel Harper -- Facebook and blackboard as learning management systems: case study / Jo Mattar -- Rethinking community? Facebook as a learning backchannel / Kate Orotn-Johnson -- Facebook at uni: mutual surveillance and a sense of belonging / Marjorie D. Kibby and Janet Fulton -- Facebook, student engagement and the'uni coffee shop' group / Tama Leaver --'I think it's mad sometimes' - unveiling attitudes to identity creation and network building by media studies students on Facebook / Kerry Gough, David Harte and Vanessa Jackson -- Should we be friends? The question of Facebook in academic libraries / Zara T. Wilkinson -- Unfriending Facebook? Challenges from an educator's perspective / Kate Raynes-Goldie and Clare Lloyd -- Role confusion in Facebook groups / Pernilla Josefsson and Fredrik Hanell -- Varying cultural conceptions of the private sphere and their impact on the use of social media networks as educational tools: a German and Chinese comparison / Xun Luo and Fergal Lenehan -- Changing Facebook's architecture / Sky Croeser -- Facebook, disability and higher education: accessing the digital campus / Katie Ellis and Mike Kent -- Facebook fatigue? A university's quest to build lifelong relationships with students and alumni / Maria L. Gallo and Kevin F. Adler -- Understanding the social media ecologies of employees within higher education institutions: a UK-based case study / Chris James Carter, Lee Martin and Claire O'Malley.
Includes bibliographical references and index.
Keywords: Facebook (Electronic resource).; Education, Higher -- Effect of technological innovations on; Education, Higher -- Computer-assisted instruction; Social media; Online social networks